A fuzzy index and severity scale to measure violence against women - Bettio, Francesca (Social indicators research, 2020)
Measuring and comparing levels of violence against women across individuals or countries are controversial exercises, and yet they remain essential to understanding the phenomenon. We develop a scale of severity of violence against women based on fuzzy set theory. The scale can be used to derive fuzzy indexes of violence which account for the prevalence, frequency and severity of violence. Unlike existing alternatives, however, the scale that we propose is based on objective information rather than subjective assessment; it is parsimonious in terms of the amount of information that it requires; and it is less vulnerable to risks of cultural bias. We exploit our scale to unravel a puzzle which arises from the largest survey of violence against women in Europe to date, namely that some of the more gender equal countries record higher prevalence rates for violence from intimate partners. We show that the puzzle is resolved once violence is weighted by severity using our scale instead of being measured by simple prevalence.